2017
DOI: 10.1016/j.clinbiomech.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of gravity-induced skin strain across the breast surface

Abstract: To reduce tension on surgical incisions it is suggested that preference should be given to medial latitudinal locations for smaller breasted women and lateral latitudinal locations for larger breasted women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Considering participant characteristics, breast volume, BMI and bust circumference displayed the strongest and most prevalent relationships with peak breast skin strain/ strain rate. This may in part support Sanchez et al 31 who reported that larger breasted women (>34D) displayed increased static breast skin strain (compared with smaller-breasted women). Willson et al 61 identified that breast skin thickness decreased with increased breast size, and thinner skin may be more distensible than thicker skin, 62 suggesting that women with larger breast volumes may be more susceptible to higher breast skin strain.…”
Section: Relationships Between Variablessupporting
confidence: 78%
See 4 more Smart Citations
“…Considering participant characteristics, breast volume, BMI and bust circumference displayed the strongest and most prevalent relationships with peak breast skin strain/ strain rate. This may in part support Sanchez et al 31 who reported that larger breasted women (>34D) displayed increased static breast skin strain (compared with smaller-breasted women). Willson et al 61 identified that breast skin thickness decreased with increased breast size, and thinner skin may be more distensible than thicker skin, 62 suggesting that women with larger breast volumes may be more susceptible to higher breast skin strain.…”
Section: Relationships Between Variablessupporting
confidence: 78%
“…Sensor coordinates were exported to Visual 3D (V.4.96.4, C-motion) and filtered (generalised cross-validatory quintic spline). 31 A reference torso segment was created, with the proximal end (origin) midway between suprasternal notch and C7 sensors, and the distal end midway between xiphoid process and T8 sensors. 40 Thirty-five inter-sensor distances were calculated for each participant, in each condition (water immersion, standing, walking and running) ( figure 1B ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations